Anthropomorphic Space: The room as a portrait of its absent subject in painting - Ralph, David (Curtin University, 2019)
This PhD explores the possibility of painting a portrait of a person by painting a room that represents or symbolises them. This is not an individual study of either portraiture or of interior decor. It is the study of both combined, into something in-between. It offers evidence to support original theory that painted domestic interiors can be anthropomorphic and deeply indicative of a living person or group of people.